The Growth performance and some blood traits in broilers under different lighting regimens - Saleh, Maytham Saad; Jassim Al-Rubaie, Muhammad Ali Makki; Khlati, Rasool Hassan (American Journal of Biodiversity, 2025)
50 chicks (unsexed) were raised from the Rose 308 broiler strain, which were prepared from one of the private hatcheries. The rearing was done on the floor and 5 treatments were used with (10) chicks per treatment. The birds were raised in cages with dimensions of 100 cm * 150 cm, with all appropriate conditions provided. Water and feed were provided freely throughout the study period. When receiving the chicks, the temperature was 32-35 and the relative humidity was 60-65. The treatments were: The first treatment was a continuous lighting system (24) hours. The second treatment: Intermittent lighting system (8 pm - 12 midnight). The third treatment: Intermittent lighting system (8 pm - 12 am). The fourth treatment: Intermittent lighting system (8 am - 12 pm). The fifth treatment: Intermittent lighting system (8 am - 12 pm). The lighting was programmed from the first day of the experiment (14 days old) until the end of the experiment (35 days old). The birds were weighed at the beginning of the experiment at the beginning of the experiment at the age of (14) days and at the end of the experiment at the age of 5 weeks for each treatment to measure body weight and weight gain and the amount of feed consumed and the feed conversion factor were measured. On day (35) of the chicks’ age, (5) ml of femoral vein blood was withdrawn and placed in tubes free of anticoagulant to prepare blood serum. This is to perform a number of blood serum tests, including glucose, cholesterol, triglycerides, HDL, LDL, vLDL, total protein, albumin protein, and thyroxine hormone. Light rationing did not negatively affect productive traits. An increase in thyroxine hormone was recorded when the lighting system was turned off for (8) hours.Light rationing system improved most of the lipid parameters in the blood serum of broilers. We recommend using other lighting periods in subsequent experiments and measuring the concentrations of important hormones such as growth hormone and melatonin hormone and Highlighting other tests such as antioxidant tests and histological tests.